2006
DOI: 10.1109/tps.2006.872173
|View full text |Cite
|
Sign up to set email alerts
|

Radiation properties and implosion dynamics of planar and cylindrical wire arrays, asymmetric and symmetric, uniform and combined X-pinches on the UNR 1-MA zebra generator

Abstract: In the following experiments, we studied implosions of different wire arrays and X-pinches produced on the 1-MA Zebra generator at the University of Nevada, Reno. Diagnostics included both spatially-resolved and time-gated X-ray imaging and spectroscopy, and laser probing. In particular, we compared planar wire arrays, to which little energy could be coupled via the conventional magnetic-to-kinetic conversion mechanism, to cylindrical wire arrays of comparable dimensions and mass. The planar wire arrays were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
27
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(30 citation statements)
references
References 32 publications
3
27
0
Order By: Relevance
“…(9). If the condition (11) can not be fulfilled, then no filament splitting for nth array wire will be performed after t j−1 , and the ablation of the nth wire will be completed at t = t (n) a , where t j−1 < t (n) a < t j .…”
Section: B Mass and Momentum Redistributionmentioning
confidence: 99%
See 3 more Smart Citations
“…(9). If the condition (11) can not be fulfilled, then no filament splitting for nth array wire will be performed after t j−1 , and the ablation of the nth wire will be completed at t = t (n) a , where t j−1 < t (n) a < t j .…”
Section: B Mass and Momentum Redistributionmentioning
confidence: 99%
“…In its turn, the implosion character depends on the planar array geometry. Below in this section we shall consider single planar wire array (SPWA) and double planar wire array (DPWA), built of a single wire row [8,9] and two wire rows [11] respectively. Two Zebra shots No.…”
Section: Wadm Modeling Of Planar Wire Arraysmentioning
confidence: 99%
See 2 more Smart Citations
“…Currently, x-ray spectra of X-pinches are collected and studied at dif ferent pulsed power machines, for exam ple, at the university-scale 1 MA Zebra device at University of Nevada, Reno [8][9][10][11][12] and Cobr a f acility a t Cornell University (CU ) [11][12], as well as at smaller devices such as at a 450 kA pulsed power device at C U [13]. It was shown that X-pinch plasm a can r each tem peratures of 2-3 keV and densities up to 10 23 cm -3 .…”
Section: Introductionmentioning
confidence: 99%